Temperature-sensitive anti-freezing material as well as preparation method and application thereof
Through the functional modification of antifreeze agents by temperature-sensitive polymer materials and the preparation of composite materials, the problem of fast salt loss in traditional antifreeze materials is solved, and the effect of efficient ice melting in winter and reducing salt loss in summer is achieved, and the resistance is extended. The service life of frozen road surfaces.
Patent Information
- Application Number
- CN202411460767.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional anti-freeze pavement materials lose fast salt in high temperature seasons, resulting in a decrease in melting ice rate. The release of sustained-release materials in extreme weather is out of control, making it difficult to effectively extend the anti-freeze effect.
The inorganic salt antifreeze is functionally modified by using temperature-sensitive polymer materials, and the temperature-responsiveness and controllable release are achieved by regulating the critical dissolution temperature of the polymer. The composite material is prepared in combination with physical blending and chemical grafting methods to optimize the salt release rate .
Ensure full release of salt in low temperature environment in winter to exert the anti-freeze effect, reduce salt loss in summer, extend the service life of the anti-freeze pavement, and improve the structural stability and durability of the material.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of antifreeze materials, and in particular to a temperature-sensitive antifreeze material and a preparation method and application thereof. Background Art
[0002] Road traffic plays an important role in modern social and economic activities. However, due to climate conditions, most of northern my country and some high-altitude areas in the south experience varying degrees of snowfall and road icing every winter. Snow and ice on the road will significantly reduce the adhesion between the vehicle and the road surface, resulting in insufficient grip of the vehicle tires, which can easily cause traffic accidents. At the same time, road icing will also significantly reduce the traffic capacity of the road network, bringing adverse effects on the development of the national economy.
[0003] In order to alleviate the problem of snow and ice on roads in winter, the current common practice at home and abroad is mainly to clear ice and snow passively afterwards, including mechanical snow removal, manual ice shoveling, and spreading snow melting agents. These methods have many disadvantages such as low efficiency, high cost, and easy secondary damage to the road surface and the environment. It is difficult to fundamentally solve the safety hazards of ice and snow roads. In recent years, the academic and engineering communities have begun to explore active anti-freeze pavement technology. By adding anti-freeze materials with ice-melting effects during the asphalt pavement laying process, the pavement is given the function of self-melting snow and anti-freezing. This type of pavement has good anti-freeze-thaw performance, is easy to construct, and has low maintenance costs. It has begun to be promoted and applied in Europe, the United States, Japan and other countries and has achieved good results.
[0004] Traditional antifreeze pavement mostly uses inorganic salts as antifreeze materials. The essence of its antifreeze effect is to use the dissolution heat absorption of salt substances and the freezing point drop of the solution to reduce the formation or adhesion of ice and snow on the road surface. Common inorganic salt antifreeze agents mainly include sodium chloride, calcium chloride, magnesium chloride, etc. Although the process of directly adding inorganic salts to asphalt mixtures is simple, there are problems such as large-scale salt loss and rapid attenuation of antifreeze effects.
[0005] In order to delay the loss of salt, domestic and foreign scholars have developed some slow-release antifreeze materials. Such materials usually use stearic acid, high-density polyethylene and other materials to coat inorganic salts, and control the migration of salt to the road surface, thereby extending the antifreeze period. However, studies have found that although slow-release materials can delay salt loss to a certain extent, "release out of control" will still occur in extreme weather such as summer rainstorms. At the same time, slow-release coating will reduce the direct contact between salt and ice and snow, resulting in a decrease in the ice melting rate. Therefore, how to minimize the ineffective loss of salt while ensuring ice melting efficiency is a key issue that needs to be solved urgently.
[0006] In view of the above problems, the present invention proposes to use thermosensitive polymer materials to functionally modify inorganic salt antifreeze agents to prepare new thermosensitive antifreeze materials. The so-called thermosensitive polymer refers to a polymer chain containing hydrophilic groups and hydrophobic groups, which exhibits solubility that changes with the ambient temperature. By introducing it into the antifreeze material system and regulating the critical solution temperature of the polymer, it is expected to achieve temperature-responsive controllable release of the antifreeze material. In the low temperature environment in winter, the thermosensitive polymer is hydrophilic, and the salt can be fully released to exert the antifreeze effect; while in the normal temperature and rainy environment in summer, the thermosensitive polymer changes from hydrophilic to hydrophobic, which inhibits the rapid loss of salt. Compared with traditional slow-release antifreeze materials, thermosensitive antifreeze materials can adaptively adjust the salt release rate according to changes in ambient temperature, while minimizing the ineffective loss of salt in the high temperature season without reducing the efficiency of ice melting in winter, thereby significantly extending the service life of antifreeze pavement. Summary of the invention
[0007] The key to thermosensitive antifreeze materials lies in the coating and regulation of the thermosensitive polymer matrix on the inorganic salt antifreeze agent. Therefore, screening suitable thermosensitive polymers is the primary task of material design. Generally speaking, thermosensitive polymers need to meet the following characteristics at the same time:
[0008] (1) Has a clear lower critical solution temperature ( ),and Falling within the winter and summer ambient temperature range, to achieve temperature-driven hydrophilic-hydrophobic transition. Range is .
[0009] (2) The ratio of hydrophilic and hydrophobic groups is moderate. The hydrophilic segment can form hydrogen bonds and other forces with inorganic salts, while the hydrophobic segment gives the polymer a certain structural stability, preventing the thermosensitive gel from swelling excessively and destroying the coating structure.
[0010] (3) It has good biocompatibility and environmental compatibility, and its degradation products are non-toxic, minimizing the negative impact on roadbed soil and surrounding ecological environment.
[0011] (4) It has excellent mechanical strength and durability, can withstand vehicle loads and environmental corrosion, and withstand at least 30 freeze-thaw cycles before failure.
[0012] (5) It is easy to prepare through conventional polymerization methods such as free radical polymerization and RAFT polymerization, with simple process and moderate cost.
[0013] Taking the above characteristics into consideration, the temperature-sensitive polymer to be selected in the present invention is polyisopropylacrylamide ( ) and their copolymers. It is a typical thermosensitive polymer. Its aqueous solution is It is hydrophilic, higher than By introducing hydrophilic polyethylene glycol ( ) monomers, which can further broaden its temperature-sensitive response window to , better fit the actual ambient temperature of the antifreeze road surface. In addition, Its copolymers have good biocompatibility, mature polymerization technology, low cost for large-scale preparation, and have been widely used in biomedicine, tissue engineering and other fields. It is also expected to achieve ideal results when introduced into the field of antifreeze materials.
[0014] After determining the thermosensitive polymer matrix, the next step is to load the inorganic salt antifreeze into the polymer network. Common composite methods include physical blending and chemical grafting. The physical blending method is simple to operate. It only requires mixing salt powder with polymer and confining the salt molecules in the polymer matrix through the interstitial confinement effect between polymer chains. However, this non-chemically bonded composite method has poor stability, and salt easily leaks from the polymer pores, making it difficult to achieve controlled release.
[0015] The chemical grafting method is to graft salt molecules onto the polymer side chain through covalent bonds to form a stable chemical composite structure. There are two main grafting methods: "grafting to" and "grafting from". The former uses the thermosensitive polymer as the main chain, and grafts salts containing specific functional groups (such as carboxyl and amine groups) onto the polymer side chain; the latter uses functionalized salts as initiators to initiate the polymerization of thermosensitive monomers, and the salt molecules are connected to one end of the synthesized polymer chain through covalent bonds. Compared with the physical blending method, the chemical grafting method can accurately control the amount of salt and inhibit salt leakage, but the reaction conditions are harsh and the grafting site is difficult to control, which may have a certain impact on the thermosensitive performance.
[0016] After weighing the pros and cons, the present invention adopts a two-step method of blending first and then grafting to prepare salt / polymer composite materials. First, the thermosensitive polymer is mixed with inorganic salts such as sodium chloride, and the initial loading is achieved through physical blending; then a small amount of silane coupling agent with functional groups is added to the system, and a chemical cross-linking structure is formed in the polymer network through a silanization reaction, further improving the structural stability of the composite material and the salt molecule retention capacity.
[0017] Optimization of material composition and ratio
[0018] In order to obtain an antifreeze composite material with excellent temperature-sensitive performance and road performance, it is necessary to optimize and screen the material composition and its ratio. The present invention intends to focus on the following influencing factors:
[0019] (1) Salt / polymer mass ratio: The amount of salt directly determines the antifreeze effect of the composite material, while the polymer content affects the thermosensitive performance. The mass ratio of the two needs to be optimized and determined on the basis of taking into account both the antifreeze performance and the controlled release performance. It is initially envisaged that the salt / polymer mass ratio is in the range of 5:1 to 10:1.
[0020] (2) Salt types and composition: Inorganic salts such as sodium chloride, calcium chloride, and magnesium chloride have their own advantages and disadvantages in terms of antifreeze performance, cost, and environmental impact. In order to balance the deicing and snowmelting effects with environmental protection requirements, it is planned to use a variety of salts in combination and select the best ratio.
[0021] (3) Polymer type and composition: by adjusting Monomer and hydrophilicity The monomer feed ratio can affect the hydrophilic and hydrophobic balance of the polymer product. The position and other temperature-sensitive properties can be regulated.
[0022] (4) Amount of silane coupling agent: -Aminopropyltriethoxysilane ( ) The effect of silanization agents on the structural stability of composite materials, and the amount of silanization agents is optimized while maintaining the temperature-sensitive properties.
[0023] In summary, by systematically conducting component screening and ratio optimization tests on antifreeze materials, it is expected that a new type of temperature-sensitive composite antifreeze material will be obtained. This material can intelligently adjust the salt release rate according to seasonal temperature changes, while exerting its own deicing and antifreeze functions while minimizing salt loss, thereby greatly extending the service life of the antifreeze pavement. DETAILED DESCRIPTION
[0024] The preparation method of the temperature-sensitive antifreeze material is as follows:
[0025] Experimental materials:
[0026] -isopropylacrylamide ( ), analytical grade, Tokyo Chemical Industry Co., Ltd.; polyethylene glycol methacrylate ( ), average molecular weight , 98%, Aladdin; -Methylenebisacrylamide ( ), 99%, Sigma-Aldrich; ammonium persulfate ( ), analytical grade, Sinopharm Group; -Tetramethylethylenediamine ( ), 99%, Aladdin; -Aminopropyltriethoxysilane ( ), , Dongyue Chemical; Sodium Chloride ( ), analytical grade, Tianjin Hengxing Chemical Reagent Manufacturing Co., Ltd.; calcium chloride ( ), analytical grade, Tianjin Fuyu Fine Chemical Co., Ltd.; anhydrous ethanol, analytical grade, Tianjin Fuyu Fine Chemical Co., Ltd.; deionized water, laboratory-made, resistivity Unless otherwise specified, all reagents were used directly without further purification.
[0027] Experimental equipment:
[0028] Digital display electric heating jacket, model: SXKW-4000, Beijing Yongguangming Medical Instrument Co., Ltd.; Rotary evaporator, model: RE-5299, Shanghai Yarong Biochemical Instrument Factory; Constant temperature magnetic stirrer, model: HJ-6A, Zhengzhou Great Wall Science and Technology Industry and Trade Co., Ltd.; Electric heating blast drying oven, model: GZX-9246MBE, Shanghai Boxun Industrial Co., Ltd. Medical Equipment Factory; Freeze dryer, model: FD-1A-50, Beijing Boyikang Experimental Instrument Co., Ltd.; Scanning electron microscope, model: S-4800, Hitachi, Japan; Fourier transform infrared spectrometer, model: Nicolet 6700, Thermoelectric Corporation, USA; Thermogravimetric analyzer, model: Q500, TA Instruments, USA; Differential scanning calorimeter, model: Q2000, TA Instruments, USA.
[0029] Synthesis of Thermosensitive Polymers:
[0030] (1) The molar ratio is 100:0-100:5 , , Dissolve in 100 mL of deionized water to form a homogeneous solution and stir until the monomer is completely dissolved.
[0031] (2) Transfer the above solution into a 250 mL three-necked flask and pass high-purity nitrogen gas through it for 30 minutes to remove dissolved oxygen.
[0032] (3) Under nitrogen protection, add initiator (0.021 g) was dissolved in 5 mL of deionized water and stirred rapidly to mix evenly.
[0033] (4) The closed reaction system was allowed to polymerize at room temperature (about 25°C) for 12 h, and the solution gradually formed a transparent hydrogel.
[0034] (5) The obtained hydrogel was cut into small pieces and dialyzed in a large amount of deionized water for 3 days, with the water replaced every 12 hours to remove unreacted monomers and initiator residues.
[0035] (6) Place the purified hydrogel in a freeze dryer and freeze dry until the gel is completely dehydrated. Collect the resulting white porous solid and seal it for later use. .
[0036] Then comes the preparation of thermosensitive polymer / inorganic salt composite materials:
[0037] (1) Weigh anhydrous and The solid powder was dissolved in 300 mL of anhydrous ethanol to prepare a homogeneous solution.
[0038] (2) Weigh 2.000g Place in a round-bottom flask, add 200 mL of the above inorganic salt solution, seal and slowly stir at room temperature for 24 h to allow the thermosensitive polymer to fully swell.
[0039] (3) Add the equivalent of 0-2.5wt% of mass , continue stirring for 6h, Fully grafted and fixed in the polymer network. Grafted on the polymer skeleton It can improve the hydrophilicity of the material and help the adsorption and loading of salt molecules.
[0040] Characterization of Thermosensitive Polymers:
[0041] (1) Morphology characterization: Take an appropriate amount The sample was fixed on the sample stage, gold-sprayed for 90 seconds, and placed The microstructure was observed at an accelerating voltage of 5.0 kV.
[0042] (2) Chemical structure characterization: right Analyze the chemical structure of Grind and mix, press to prepare transparent discs, place in infrared spectrometer for scanning, scanning range 4000-400 , resolution 4 , scan times 32 times.
[0043] (3) Characterization of temperature-sensitive performance: test The lower critical solution temperature ( ). Accurately weigh 5.0 mg of sample into an aluminum crucible, scan at a temperature range of 10-50°C at a heating rate of 2°C / min, with a nitrogen flow rate of 50 mL / min, record the heat flow curve of the sample, and determine the endothermic peak on the curve. .
[0044] Characterization of Thermosensitive Polymer / Inorganic Salt Composites:
[0045] use , , , Other methods The morphology, structure, composition and thermal properties of the samples were characterized under the same conditions as before. In addition, an energy dispersive X-ray spectrometer ( ) The elemental composition and distribution of the composite materials were analyzed to examine the loading and dispersion of the inorganic salts in the polymer matrix.
[0046] Optimization of key properties of composite materials:
[0047] Optimization of monomer ratio:
[0048] Effect of monomer ratio on the properties of thermosensitive polymers , which in turn affects the temperature response characteristics of the composite material. The molar ratio is the object of investigation, and the fixed amount of inorganic salt is The weight of the samples was 10 times that of the raw materials, and 4 monomer ratio levels were set. Three samples were prepared for each level. The swelling rates of the samples after immersion at different temperatures for 24 hours were tested and the average values were calculated. )for:
[0049] ;
[0050] in is the mass of the sample after swelling, is the mass of the sample before swelling. The experimental results are shown in Table 1.
[0051] ;
[0052] As can be seen from Table 1, the higher the content, the higher the swelling rate of the composite material in the range of 5-45°C, and the weaker the temperature responsiveness. When it is 100:2, the composite material has a high swelling rate (>1000%) in the range of 5-25°C, and the swelling rate decreases significantly (<500%) at temperatures above 35°C, indicating that it has undergone a significant hydrophilic-hydrophobic transition near room temperature, which is in line with the design concept of self-dissolving in winter and self-sealing in summer for pavement materials. Therefore, the subsequent study fixed the molar ratio to 100:2.
[0053] Optimization of inorganic salt dosage:
[0054] In order to optimize the dosage of inorganic salts, the The quality ratio Effect on the properties of composite materials. Multiple levels (1:1, 2:1, 5:1, 10:1, 15:1, 20:1) were set, and 3 samples were prepared for each level. The swelling ratio of the samples at 0-30°C and the compressive strength at 25°C were tested. The results are shown in Table 2.
[0055] ;
[0056] The results show that with the increase of the amount of inorganic salt, the swelling rate and mechanical properties of the composite material are improved. When the ratio is 15:1, the comprehensive performance is the best, with excellent low-temperature swelling performance and room-temperature mechanical properties. Therefore, the amount of inorganic salt is selected to be 15 times the mass.
[0057] Optimization of dosage:
[0058] As a silane coupling agent, it can enhance the structural stability of composite materials. It plays a role in cross-linking and strengthening in the thermosensitive polymer network. Its dosage will affect the structural stability and salt molecule retention capacity of the composite material. The molar ratio is 100:2, the amount of inorganic salt is 15:1, and the setting Dosage The weight loss rate and compressive strength retention rate of the samples after immersion in 25°C water for 7 days were tested. The results are shown in Table 3.
[0059] ;
[0060] As can be seen from Table 3, adding a small amount of It can reduce the weight loss rate of composite materials and improve the retention rate of mechanical properties. When the dosage is 2wt%, the performance is better. When the dosage is greater than 2.0wt%, the weight loss rate and compression strength retention rate decrease. This may be due to excessive Cross-linking makes the polymer network too dense, limiting the swelling capacity of the material. Dosage 2wt% of mass.
[0061] From the perspective of material synthesis, this invention introduces in detail a method for preparing a new type of temperature-sensitive antifreeze composite material. and The thermosensitive polymer was prepared by free radical copolymerization. The inorganic salt mixture is loaded into the polymer network by the swelling method, and then After silanization treatment, a temperature-sensitive antifreeze composite material is finally obtained.
[0062] By adjusting the monomer ratio, inorganic salt dosage and The dosage was optimized and the best preparation conditions were determined: The molar ratio is 100:2, and the amount of inorganic salt is 15 times the mass, The dosage is 2wt%. The prepared composite material has good temperature responsiveness, antifreeze performance and structural stability, and has potential application value in road engineering.
[0063] The following examines its temperature response characteristics, antifreeze performance, mechanical properties and durability.
[0064] The microstructure of the composites was observed using a JEOL JSM-7500F field emission scanning electron microscope. Sample preparation: The dried composite powder was fixed on the sample stage and gold-sprayed for 90 seconds to improve conductivity. The scanning voltage was 3.0 kV and the magnification ranged from 500 to 10,000 times. In order to quantify the pore size distribution of the composites, we counted the pore sizes at different magnifications, and the results are summarized in Table 4.
[0065] ;
[0066] As can be seen from Table 4, the temperature-sensitive antifreeze composite material has a multi-scale pore size distribution, ranging from tens of nanometers to several microns, and the average pore size decreases with the increase of magnification. This porous structure is conducive to the water absorption and swelling of the material and the diffusion of salt ions, which is the key to achieving temperature-sensitive and antifreeze properties. The increase in porosity also indicates that the material has a higher specific surface area, which is conducive to improving performance.
[0067] The phase composition of the composite material was analyzed using a Bruker D8Advance X-ray diffractometer. Test conditions: Cu Kα ray, tube voltage 40kV, tube current 40mA; scanning range 5°-80°, step length 0.02°, scanning speed 2° / min. PNIPAM-PEGMA, composite material and pure , The 2θ angles of the main diffraction peaks and the corresponding diffraction intensities are summarized in Table 5.
[0068] ;
[0069] As can be seen from Table 5, the XRD spectrum of PNIPAM-PEGMA only shows a broad peak at 2θ≈20°, indicating that it is an amorphous polymer. and They show their own characteristic diffraction peaks. In the composite material, it can be observed and The characteristic diffraction peaks of the inorganic salts were found, but the peak intensity was lower than that of the pure substance, indicating that the inorganic salts had been successfully embedded in the polymer matrix and existed in a smaller crystal size.
[0070] The chemical structure of the composite material was analyzed using a Thermo Nicolet 6700 Fourier transform infrared spectrometer. Sample preparation: Mix the dried sample with KBr powder in a ratio of 1:100, grind evenly and press into tablets. Test conditions: Scanning range 4000-400cm , resolution 4cm , scanning times 32. The wave numbers of the main absorption peaks and the corresponding group assignments are listed in Table 6.
[0071] ;
[0072] It can be seen from Table 6 that the composite material has A new absorption peak appeared at 3440 cm-1, corresponding to the vibration of Si-O-Si and Si-OC, indicating that the silane coupling agent has been successfully grafted onto the polymer chain. The absorption peak intensity at increases, indicating that the hydrophilicity of the material is improved.
[0073] Thermosensitive polymers The swelling / contraction behavior is obvious near the surface, and the swelling property of the composite material directly affects its antifreeze effect. This section studies the effect of inorganic salt content on the temperature response swelling property of the composite material.
[0074] Experimental method: Cut the dried composite material sample into small pieces of 10mm × 10mm × 2mm, weigh them, and soak them in deionized water at 0-55°C for 24h. After taking them out, use filter paper to gently absorb the surface moisture, weigh them, and calculate the swelling rate. The results are shown in Table 7.
[0075] ;
[0076] It can be seen from Table 7 that with the increase of salt content, the swelling rate of the composite material at low temperature increases slightly, while the swelling rate at high temperature decreases more significantly. When the temperature is below 30 ° C, the composite material maintains a high swelling rate, reflecting good temperature responsiveness.
[0077] The phase transition behavior of the composite material was characterized by using a PerkinElmer DSC 8000 differential scanning calorimeter. Experimental method: About 5 mg of dry sample was weighed into an aluminum crucible and scanned in the range of 10-60°C at a heating rate of 5°C / min under nitrogen protection. The heat flow curve of the sample was recorded and the endothermic peak was used to determine the phase transition behavior of the composite material. . Composites with different salt contents Listed in Table 8.
[0078] ;
[0079] It can be seen from Table 8 that with the increase of inorganic salt content, the This is consistent with the swelling performance test results, indicating that the introduction of inorganic salts has a certain regulatory effect on the temperature responsiveness of polymers.
[0080] The compressive strength was used as an evaluation index to examine the strength change of the composite material before and after freeze-thaw cycles and evaluate its antifreeze performance.
[0081] Experimental method: The composite material was prepared into a Φ50mm × 50mm cylindrical specimen, and demolded after curing at room temperature for 24 hours. The initial compressive strength was measured, and then 10 freeze-thaw cycles were performed. The compressive strength and strength retention rate of the composite materials with different salt contents are listed in Table 9.
[0082] ;
[0083] It can be seen from Table 9 that the antifreeze performance of the composite material is significantly improved with the increase of inorganic salt content. When the salt: polymer mass ratio is 10:1 and 15:1, the strength retention rate reaches 90%, indicating that the composite material has good antifreeze-thaw ability.
[0084] The tensile properties of the composite materials were tested using an Instron 5567 universal material testing machine. Experimental method: dumbbell-shaped specimens were prepared according to GB / T 1040.2-2006 standard, and the tensile rate was 20 mm / min. The test results are summarized in Table 10.
[0085] ;
[0086] The compression properties of the composite materials were tested using an Instron 5567 universal material testing machine. Experimental method: The sample was prepared into a Φ10mm × 10mm cylinder, and the compression rate was 2mm / min. The compression strength results are shown in Table 11.
[0087] ;
[0088] The low-temperature bending test was used to evaluate the effect of composite materials on the low-temperature performance of asphalt mixture. Experimental method: The composite materials were added to AC-13 asphalt mixture to prepare beam specimens, and three-point bending tests were carried out at -10°C. The test results are shown in Table 12.
[0089] ;
[0090] The addition of composite materials significantly improves the low-temperature performance of asphalt mixtures, but this effect shows nonlinear characteristics. With the increase of the amount of composite materials, the low-temperature flexural strength and ultimate flexural strain both show a trend of increasing first and then decreasing. At a dosage of 5wt%, the material performance reaches the best, the low-temperature flexural strength increases to 12.0 MPa, and the ultimate flexural strain increases to 4200, which are about 41.2% and 68% higher than those without addition. This shows that the addition of composite materials in appropriate amounts can effectively enhance the low-temperature cracking resistance of asphalt mixtures. However, when the dosage exceeds 5%, the performance begins to decline, indicating that excessive addition may lead to material performance degradation. The composite material can significantly improve the low-temperature performance of asphalt mixtures, which is of practical significance for improving the service life and safety of roads.
[0091] The present invention systematically characterizes and evaluates the performance of the prepared temperature-sensitive antifreeze composite material. The microstructure and chemical composition of the composite material were confirmed by means of SEM, XRD and FTIR. The temperature response performance test shows that the composite material has good swelling / shrinking behavior in a range close to room temperature. The antifreeze performance evaluation shows that the composite material has excellent anti-freeze-thaw ability and is suitable for use in cold areas. The mechanical property test results show that an appropriate amount of inorganic salt can improve the strength and hardness of the material, but an excessive amount will affect the toughness. The compatibility evaluation with asphalt mixture shows that the addition of the composite material can improve the anti-skid and low-temperature performance of the road surface, providing a reliable basis for its application in road engineering.
Claims
1. A temperature-sensitive antifreeze material, characterized in that: The material comprises: polyisopropyl acrylamide-polyethylene glycol methacrylate copolymer (PNIPAM-PEGMA), inorganic salt antifreeze agent: a mixture of sodium chloride and calcium chloride, and silane coupling agent: gamma-aminopropyl triethoxysilane (KH550); the component ratio is: the molar ratio of PNIPAM and PEGMA monomers is 100:0-100:5, the mass ratio of inorganic salt to PNIPAM-PEGMA is 15:1, wherein the molar ratio of NaCl to CaCl2 is 3:1, and the amount of KH550 silane coupling agent is 0-2.5wt% of the mass of PNIPAM-PEGMA.
2. The temperature-sensitive antifreeze material according to claim 1, characterized in that: The preparation method of the polyisopropylacrylamide-polyethylene glycol methacrylate copolymer (PNIPAM-PEGMA) comprises the following steps: (1) , , Dissolve in 100 mL of deionized water to form a homogeneous solution and stir until the monomer is completely dissolved; (2) Transfer the above solution to a 250 mL three-necked flask and pass high-purity nitrogen gas for 30 minutes to remove dissolved oxygen; (3) Under nitrogen protection, add initiator (0.021 g) was dissolved in 5 mL of deionized water and stirred rapidly to mix evenly; (4) The closed reaction system was allowed to polymerize at room temperature (25°C) for 12 h, and the solution gradually formed a transparent hydrogel; (5) Cut the obtained hydrogel into small pieces and dialyze them in a large amount of deionized water for 3 days, replacing the water every 12 hours to remove unreacted monomers and initiator residues; (6) The purified hydrogel is placed in a freeze dryer and freeze-dried until the gel is completely dehydrated. The resulting white porous solid is collected and sealed for later use; this is recorded as .
3. The temperature-sensitive antifreeze material according to claim 2, characterized in that: The preparation steps also include: (7) Add KH550 silane coupling agent at a dosage of 2 wt% of the mass of PNIPAM-PEGMA and continue stirring for 6 h; (8) Remove ethanol by vacuum distillation at 50°C until it becomes a paste, and then dry with forced air at 60°C for 12 h; (9) The dried material was pre-frozen at -40°C for 6 h and then freeze-dried under vacuum for 72 h to obtain a white powdery composite material.
Citation Information
Patent Citations
Thermo-sensitive type ultrafiltration membrane and preparation method thereof
CN103418255A
Temperature-control-based anti-freezing material and preparation method and application thereof
CN107686278A
Random copolymer modified powder type anti-freezing material with rapid temperature response and preparation method of random copolymer modified powder type anti-freezing material
CN115724609A